(untitled) (Singaporean Journal of Business Economics and Management, 2014)
Privatization has been the most controversial policy dominating the political agenda of many countries around the world. For instance, in the 1980s privatization were the policy choice and preferences as well as the new wave of conservative market reforms beginning in the west with the Thatcher government in the United Kingdom in 1979 and the Regan government in the United States the following year. In Africa it has remained a highly controversial, a subject of debate and politically risky. After her independence, Nigeria, engaged in the expansion of the public sector in the first, second and third development plans following the keynesian paradigm.The present drive towards privatizations is the inability of the Keynesian paradigm to deal decisively with the worldwide economic crises and the various economic system adopted in Nigeria Privatization of public enterprises in Nigeria is believed will bring about an end to Inefficiency, Balance of payment deficit, Low performance, Indiscipline, mismanagement of finance, attract Foreign and local Investment which will integrate the country in the globalization process and bring about competitive system, quality, and low price, better choice and satisfaction of goods and services. This paper seeks to discuss the major theoretical under pining of the concept of privatization, its major ideas and proponents in a thematic form. The paper concludes by positing that from literatures on privatization three things are clear. First, for privatization to take place there must be in existence public enterprises, which need to convert into private enterprises. Secondly, there is the reasoning that private ownership or control or management would be better than public ownership. Finally, privatization is premised on the fact that there are problems with public ownership of enterprises and privatization is part and parcel of a reform agenda to turn around these enterprises so that they can deliver goods and services more efficiently and effectively. As we shall show later, this kind of reasoning is ideologically loaded and cannot be substantiated by the existential reality of Nigeria.